1996
DOI: 10.1104/pp.111.4.1153
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamoyltransferases Involved in the Accumulation of Caffeic Acid Esters in Gametophytes and Sporophytes of Equisetum arvense

Abstract: Four hydroxycinnamoyltransferases from Equisefum arvense L. were studied that catalyze the formation of mono-Ocaffeoylmeso-tartrate, di-O-caffeoyl-meso-tartrate, 5-Ocaffeoylshikimate (dactylifrate), and 5-Ocaffeoylquinate (chlorogenate). l h e enzymes were classified as coenzyme A (COA)-ester-dependent acyltransferases (EC 2.3.1), i.e. hydroxycinnamoyl-CoAmeso-tartrate hydroxycinnamoyltransferase (CTT), hydroxycinnamoyl-CoA:caffeoyl-meso-tartrate hydroxycinnamoyltransferase (CCT), hydroxycinnamoyl-CoAshikimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Rye primary leaves responded most sensitively within 4 d after emerging from the coleoptile (Reuber et al 1996;Burchard, Bilger & Weissenböck 2000), and UV-B-dependent flavonoid accumulation in Arabidopsis was restricted to the early stages of leaf development (Lois 1994). HCT activities, involved in phytoalexin biosynthesis, were also developmentdependent in various systems, for example, wheat coleoptiles (Louis & Negrel 1991) and Equisetum sporophytes (Hohlfeld, Veit & Strack 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Rye primary leaves responded most sensitively within 4 d after emerging from the coleoptile (Reuber et al 1996;Burchard, Bilger & Weissenböck 2000), and UV-B-dependent flavonoid accumulation in Arabidopsis was restricted to the early stages of leaf development (Lois 1994). HCT activities, involved in phytoalexin biosynthesis, were also developmentdependent in various systems, for example, wheat coleoptiles (Louis & Negrel 1991) and Equisetum sporophytes (Hohlfeld, Veit & Strack 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Pure chicoric acid is a white powder (Synoradzki et al, 2005; personal observation), and now available as a purified standard via numerous chemical companies (e.g., Cerilliant Chemical Company, Indofine Chemical Company, Inc., Sigma-Aldrich Co, LLC, etc.). The most abundant natural form is L-chicoric acid [i.e., (-)-chicoric acid, 2,3-dicaffeoyl-L-tartaric acid, 2,3- O -dicaffeoyltartaric acid, 2R,3R- O -dicaffeoyltartaric acid, or di- E -caffeoyl-(2R-3R)-(-)-tartaric acid] and has been reported in the majority of the plants listed in Table 1, but the stereoisomer meso -chicoric acid (i.e., dicaffeoyl- meso -tartaric acid or di- E -caffeoyl-(2R-3S)-(-)-tartaric acid) has also been reported at a lesser levels in horsetail sprouts ( Equisetum arvense L.) (Veit et al, 1991, 1992; Hohlfeld et al, 1996), iceberg lettuce ( Lactuca sativa L.) (Baur et al, 2004; Luna et al, 2012), and purple coneflower ( Echinacea purpurea L. Monech) (Perry et al, 2001). …”
Section: Identification Synthesis and Biosynthesis Chicoric Acidmentioning
confidence: 99%
“…Snook et al (1994) showed that a small amount of L-chicoric acid in peanut leaf terminal methanol extract isomerized into meso -chicoric acid at room temperature. Although three accounts from a single research group confirmed by Nuclear Magnetic Resonance (NMR) the tartaric acid structure of purified meso -chicoric acid of horsetail barren sprouts (Veit et al, 1991, 1992; Hohlfeld et al, 1996), an independent report found L-chicoric acid, but no meso -chicoric acid in horsetail (Hasegawa and Taneyama, 1973). …”
Section: Identification Synthesis and Biosynthesis Chicoric Acidmentioning
confidence: 99%
“…A S. lycopersicum HQT was also shown to be involved in the formation of diCQA from CQA ( Moglia et al, 2014 ). In A. glabrata and Equisetum arvense , it was shown that CTA is synthesized through condensation of a caffeoyl-CoA with tartaric acid which is a typical mechanism of the BAHD family members ( Hohlfeld et al, 1996 ; Sullivan, 2014 ). Furthermore chicoric acid was demonstrated in vitro to be synthesized by transfer of a caffeoyl moiety of caffeoyl-CoA to CTA in E. arvense ( Hohlfeld et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%